Analysis of Physical Condition in Spartan Kids Athletics Members - Tamba, Nelsi Betrika, Sukendro; Putra, Anggrawan Janur (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2025)
This study aims to determine the physical condition of Spartan Kids Athletics members. This research is a quantitative descriptive research with a survey method with TKJI measurement techniques. The population in this study was 18 athletes from Spartan Kids Athletics, with details of 10 athletes aged 10-12 years and 8 athletes aged 13-15 years. The sampling technique used is total sampling. The instruments in this study were speed (Sprint), arm and shoulder power (pull up), abdominal power (sit up), leg power (vertical jump), and endurance (medium distance running). Data analysis uses descriptive percentages. The results of the data calculation obtained the results of the average physical condition of Spartan Kids Athletics members aged 10-12 years from 10 people with a value of 16 points and included in the medium category. The results of the data calculation obtained the results of the average physical condition of Spartan kids athletics members aged 13-15 years from 8 people with a value of 15.75 points and were included in the medium category. Based on the results of the research and data calculations that have been carried out, it can be concluded that the level of physical condition of Spartan Kids Athletics members aged 10-12 years and ages 13-15 years is in the medium category.